1978
DOI: 10.3146/i0095-3679-5-1-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 2,4-DB on Yield and Pod Development in Peanuts

Abstract: The herbicide 2,4-DB [4-(2,4-dichlorophenoxy) butyric acid] was not readily absorbed by peanut (Arachis hypogaea L.) leaves, was not accumlated in the nut at harvest and was very slowly metabolized to 2, 4-D (2,4-dichlorophenoxyacetic acid). In contrast, pigweed (Amaranthus retroflexus L.) readily absorbed the 2,4-DB and rapidly converted it to 2,4-D. The 2,4-D was subsequently translocated to the apical regions of the pigweed and resulted in severely reduced growth or death. Applications of 0.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
21
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 0 publications
2
21
0
Order By: Relevance
“…Knauft et al (12) noted similar results from paraquat application and attributed grade differences to method of maturity sampling from nontreated border peanut. Other herbicides have been shown to effect peanut yield and pod development (11). Previous research has shown that registration of AC 263,222 would provide growers with an effective broadleaf and perennial nutsedge herbicide (17).…”
Section: Resultsmentioning
confidence: 99%
“…Knauft et al (12) noted similar results from paraquat application and attributed grade differences to method of maturity sampling from nontreated border peanut. Other herbicides have been shown to effect peanut yield and pod development (11). Previous research has shown that registration of AC 263,222 would provide growers with an effective broadleaf and perennial nutsedge herbicide (17).…”
Section: Resultsmentioning
confidence: 99%
“…2,4-DB is not readily absorbed nor translocated (8,14). Peanut seedlings held at 100% relative humidity retained 80% of the amount of 2,4-DB applied on the leaf surface (9). The 2,4-D, formed from beta-oxidation within the treated leaf, appeared to be the more mobile product (9).…”
mentioning
confidence: 91%
“…However, beta oxidation within plant tissue produces 2,4-D which is phytotoxic (9,14). 2,4-DB is not readily absorbed nor translocated (8,14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Visual injury symptoms of 2,4-DB can be observed in the form of rolled or elongated foliage [41,42].…”
Section: Introductionmentioning
confidence: 99%